Jejunal diverticular perforation in an acute abdomen: A case report - Banerjee, Divya Jyoti; Chauhan, Himesh (Indian Journal of Case Reports, 2024)
Jejunal diverticula are acquired pseudodiverticula that occur due to the herniation of the mucosa and submucosa through the weakest site of the muscularis propria of the bowel wall. Perforation of inflamed diverticula is a rare phenomenon that needs immediate operative intervention, an exploratory laparotomy along resection and anastomosis. Here, we report the case of a 50-year-old female with jejunal diverticular perforation. The patient presented with complaints of generalized abdominal pain associated with abdominal distension, constipation, and vomiting. Generalized abdominal tenderness, guarding, and rigidity were present. Ultrasound was suggestive of sealed bowel/diverticular perforation with localized peritoneal collection. The patient was taken for exploratory laparotomy which showed a jejunal diverticulum along with perforation. It was decided to do resection and anastomosis of the affected segment. The follow-up was uneventful. Since perforation of the jejunal diverticula is a rare phenomenon, the diagnosis needs to be considered in patients presenting with an acute abdomen.